Effect of titanium additions upon microstructure and properties of precipitation-strengthened Fe-Ni-Al-Cr ferritic alloys. (15th April 2017) - Rawlings, Michael J.S.; Liebscher, Christian H.; Asta, Mark; Dunand, David C.
Abstract: Various amounts of Ti (0, 2, 4 and 6 wt%) is added to a ferritic alloy with a nominal composition of Fe–10Cr–10Ni–6.5Al–3.4Mo–0.25Zr–0.005B (wt%) (FBB8). The microstructure and composition of the matrix and precipitate phases are characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). For the Ti-modified steels, the bcc ferritic matrix is strengthened by submicron L21 -Ni2 TiAl-type precipitates which contain (i) Fe-inclusions with the precipitates' overall diameters ranging from 100 to 500 nm for both FBB8-4 wt%Ti and FBB8-6 wt%Ti, or (ii) B2-NiAl sub-precipitates with an average diameter of 50–100 nm for FBB8-2 wt%Ti. By contrast, the Ti-free FBB8 alloy contains B2-NiAl precipitates with Fe-inclusions. The four FBB8-Ti alloys were subjected to creep experiments at 700 °C in the stress range of 60–300 MPa. Threshold stresses for all studied compositions were observed, ranging from 69 to 179 MPa, with the most creep-resistant alloy being FBB8-2Ti with L21 /B2 precipitates. Based on these mechanical results and detailed electron microscopy observations, the creep mechanism is rationalized to be general dislocation climb with repulsive elastic interaction between coherent precipitates and the matrix dislocations. Graphical abstract: Image 1